Impact of Agriculture, Manufacturing, Commodity Producing Sectors and Service Sectors on GDP Growth Rate: Empirical Evidence from Pakistan 1994-95 to 2021-22 - Bushra Zaman,; Prof. Dr. Muhammad Niamat Ullah,; Saima Munir,; Shehla Mazhar, (Al-Qanṭara, 2023)
Purpose: The present study is aimed at assessing the economic significance of Agriculture (At), Manufacturing (Mt), Commodity Producing (CPSt), and Service Sectors (St) towards GDP (Qt) growth rate of Pakistan. Method: Time series data ranges from 1994-95 to 2021-22 from authenticated sources were utilized for present research study. Econometric analysis i.e Augmented Dickey Fuller Test, Log-linear response functions, Autoregressive Distribute Lags Model, Bound Test, relationships, Co-integration and Long Run form for estimating short and long run relationships, Lagrange Multiplier (LM) Test, Normality Test, Granger Causality Test, Impulse Response Function and Walt Test were employed.Results: Findings revealed that respective variables (Qt, Mt, St) were stationary at level I(0) order of integration and respective variables (At, and CPSt) at 1st difference I(1). ARDL examined co-integrating relationships between tested variables in the model. F Stat value of Bound Test is worked out 4.97, which were more than upper bound’s critical value, hence by rejecting HO hypothesis and accepting HI, long run association established between tested parameters. The value of Co-integrating equation is significant (P>0.05) and negative (-0.954981), depicting adjustment speed towards short and long run equilibrium. No serial correlation was observed in the model. Findings revealed uni-directional causal relationship between GDP and Services (P>0.05), between Commodity Producing Sector (CPS) and Services (P>0.05) and between Manufacturing Sector and Services (P>0.1) indicating long-term relationship in the cointegration test. Impulse Response Analysis indicated negative as well as positive responses; shock to GDP noticed symmetric impact on Agriculture, Manufacturing, Commodity Producing and Services Sectors of Pakistan in short run and long run. Wald test confirmed the significance of independent variables for a model. Conclusion: Results revealed positive and significant impact of Agriculture Sector (At), Manufacturing Sector (Mt), Commodity Producing Sector (CPSt) and Services Sector (St) on GDP (Qt) Growth Rate of Pakistan over a period of time 1994-95 to 2021-22. Implications: The study concludes the implications in terms of causes and effects of Agriculture, Manufacturing, Commodity producing and Service sectors, which could be overcome and significantly impacted on economic growth through maximum utilization of cultivable land to address under utilization of lands, division of labour force to address unemployment, capital accumulation to address poverty and entrepreneurial skills to address issues in means of communication and transport. Keywords: GDP, Impact of sectors, ADF, causality, Co-integration, Long run & Pakistan.